Tas Sling Bag dengan Memanfaatkan Hasil Eksplorasi Material Bonggol Jagung: Tas Sling Bag bonggol jagung - Riya Astuti; Andry Masri (Jurnal Desain Produk Nasional, 2023)
This research is about the design of a sling-bag made from corncob for young people aged 18-25 years,as the result of utilized corncob exploration that has done at the Craftindo Kreasi Workshop in Bandung. This research is motivated by the opportunity for the industry to offer fashion commodities that have been underdeveloped, because so far the industry has focused on furniture products, and merchandise. The method used in this design is an experiment-based iterative method, namely by conducting direct trials at the workshop during the design process. At the end of this research, a prototype of a sling bag product with corncob material using bending and lamination techniques was produced. The novelty of this research is the bag made from corncobs.Keywords: sling bag, corn cob